Bag-1L is a Stress-withstand Molecule Prevents the Downregulation of Mcl-1 and c-Raf Under Control of Heat Shock Proteins in Cisplatin Treated HeLa Cervix Cancer Cells - Çoker Gürkan, Ajda; Eralp, Tuğçe Nur; Dinler Doğanay, Gizem; Palavan Unsal, Narçin; ARISAN, ELİF DAMLA; YERLİKAYA, PINAR OBAKAN; KILBAŞ, PELİN ÖZFİLİZ (Asian Pacific Organization Cancer Prevention, Apjcp Head Office, Korean Natl Cancer Center, 323 Ilan -Ro, Ilsandong-Gu, Goyang-Si, Gyeonggi-Do, 410-769, South Korea, 2014)
Background: Cisplatin, a DNA damaging agent, induces apoptosis through increasing DNA fragmentation. However, identification of intrinsic resistance molecules against Cisplatin is vital to estimate the success of therapy. Bag-1 (Bcl-2-associated anthanogene) is one anti-apoptotic protein involved in drug resistance impacting on therapeutic efficiency. Elevated levels of this protein are related with increase cell proliferation rates, motility and also cancer development. For this reason, we aimed to understand the role of Bag-1 expression in Cisplatin-induced apoptosis in HeLa cervix cancer cells. Cisplatin decreased cell viability in time-and dose-dependent manner in wt and Bag-1L+HeLa cells. Although, 10 mu M Cisplatin treatment induced cell death within 24h by activating caspases in wt cells, Bag-1L stable transfection protected cells against Cisplatin treatment. To assess the potential protective role of Bag-1, we first checked the expression profile of interacting anti-apoptotic partners of Bag-1. We found that forced Bag-1L expression prevented Cisplatin-induced apoptosis through acting on Mcl-1 expression, which was reduced after Cisplatin treatment in wt HeLa cells. This mechanism was also supported by the regulation of heat shock protein (Hsp) family members, Hsp90 and Hsp40, which were involved in the regulation Bag-1 interactome including several anti-apoptotic Bcl-2 family members and c-Raf.
Keywords: Bag-1; Hsp family; cervical cancer; apoptosis; drug resistance; Chaperone Activity; Expression; Apoptosis; Carcinoma; Bcl-2; Bag1; Survival; Pathway; Growth; Genes